Implementasi Peran Saksi Dalam Pengungkapan Perkara Tindak Pidana Pencemaran Nama Baik Melalui Elektronik - Masril; Vivi Arfiani Siregar; Kms Novyar Satriawan F (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2025)
This study aims to analyze the implementation of the role of witnesses in disclosing criminal cases of defamation through electronic media, as well as the factors affecting the effectiveness of the evidentiary process. This research employs an empirical legal research method with a qualitative descriptive approach through interviews, observations, and documentation studies. The results indicate that witness testimony plays an important role in strengthening electronic evidence in the disclosure of defamation crimes. However, its implementation still faces several obstacles, such as the limited availability of witnesses who directly know the incident, the complexity of digital evidence examination, and the lack of public understanding regarding legal provisions on electronic information and transactions. Therefore, it is necessary to improve the capacity of law enforcement officials and increase public legal awareness so that the process of evidence examination and law enforcement can be carried out more effectively.